2021
DOI: 10.1016/j.isci.2021.102310
|View full text |Cite
|
Sign up to set email alerts
|

Phylobioactive hotspots in plant resources used to treat Chagas disease

Abstract: Summary Globally, more than six million people are infected with Trypanosoma cruzi , the causative protozoan parasite of the vector-borne Chagas disease (CD). We conducted a cross-sectional ethnopharmacological field study in Bolivia among different ethnic groups where CD is hyperendemic. A total of 775 extracts of botanical drugs used in Bolivia in the context of CD and botanical drugs from unrelated indications from the Mediterranean De Materia Medic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…No cytotoxicity was detected for falcarindiol up to 100 µM (26 µg/mL), similarly to fraction 1 (CC 50 = 28 µg/mL), while it effectively reduced T. cruzi infection to undetectable levels (maximum activity higher than 100%, like for fraction 1), thus demonstrating that this molecule is highly selective towards T. cruzi amastigotes. In the only studies available on falcarindiol's trypanocidal effects, Salm et al [34] reports that the polyacetylene isolated from Sium sisarum L. had no inhibitory effect on T. cruzi, while Mennai et al [35] describes a low anti-trypanosomal activity of this constituent identified in Pituranthos battandieri Maire. Nevertheless, the former performed antiproliferation assays on T. cruzi epimastigotes (IC 50 > 50 µM) and trypomastigotes (0% parasite release inhibition at 5 µM), and the latter assayed on epimastigote forms of T. cruzi (IC 50 = 121.8 µM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No cytotoxicity was detected for falcarindiol up to 100 µM (26 µg/mL), similarly to fraction 1 (CC 50 = 28 µg/mL), while it effectively reduced T. cruzi infection to undetectable levels (maximum activity higher than 100%, like for fraction 1), thus demonstrating that this molecule is highly selective towards T. cruzi amastigotes. In the only studies available on falcarindiol's trypanocidal effects, Salm et al [34] reports that the polyacetylene isolated from Sium sisarum L. had no inhibitory effect on T. cruzi, while Mennai et al [35] describes a low anti-trypanosomal activity of this constituent identified in Pituranthos battandieri Maire. Nevertheless, the former performed antiproliferation assays on T. cruzi epimastigotes (IC 50 > 50 µM) and trypomastigotes (0% parasite release inhibition at 5 µM), and the latter assayed on epimastigote forms of T. cruzi (IC 50 = 121.8 µM).…”
Section: Discussionmentioning
confidence: 99%
“…The use of different morphological forms of the parasite may explain the divergent reports on the anti-T. cruzi activity of falcarindiol, as compounds can present disparate activity against trypomastigotes, intracellular amastigotes, and epimastigotes [27]. Despite variations in falcarindiol's activity being potentially due to the different life stages of T. cruzi, the concentration could also account for the different results: falcarindiol was only active against epimastigotes at high concentrations (>50 µM) [34,35], and only a low concentration (5 µM) was tested against trypomastigotes in the release assay [34].…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by Ottoʼs molecular pharmacognosy and openness for ethnobotanical studies, and our positive experience in his lab at ETH, Marco Leonti and I continue to carry out ethnopharmacological studies to the present day. I recently went back to the Amazonian forests, this time working on Chagas disease [11,12]. Natural products will never stop inspiring drug development, and pharmacognosy will survive if humanity manages to protect the biogenetic resources.…”
Section: Coda: the Revival Of Natural Product Research And The Threat Of Losing Biogenetic Resourcesmentioning
confidence: 99%
“…Throughout the history of mankind, natural products have been decisive for the discovery of new drugs, since they have enormous structural diversity as compared to conventional synthetic molecules and the screening of these natural sources remains one of the most attractive routes for this purpose [ 6 , 7 ]. Various plant species have been tested in the search for natural products to combat Chagas disease caused by T. cruzi , exhibiting in many cases high trypanocidal activity and low toxicity [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%